TRANSFORMASI PEKARANGAN PRODUKTIF MELALUI MICROGREENS, PUPUK ORGANIK CAIR, DAN PESTISIDA NABATI DI NAGARI SIMAWANG - Mildawati Mildawati; Solfiyeni; Aadrean; Syamsuardi; Hafiza Khairunnisa; Siti Sovia; Zahra Hikmah Lubis; Zahra Ramadhani (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2026)
Nagari Simawang has strong agricultural potential, yet the community faces limited yard utilization, dependence on costly chemical inputs, and low awareness of sustainable farming practices. This community service program aimed to enhance the knowledge and skills of residents, particularly women’s groups (PKK) and farmer groups, through practical and eco-friendly agricultural innovations. Activities were conducted in January 2026 using counseling, demonstrations, and participatory training. The program introduced three innovations: (1) microgreens cultivation using cocopeat media for limited spaces; (2) liquid organic fertilizer production from rice washing water and onion peel waste; and (3) botanical pesticide preparation from mature papaya leaves. The results indicated high participant enthusiasm, active engagement, and improved ability to independently apply the introduced techniques. In addition, participants gained greater awareness of household waste utilization and sustainable farming systems. Overall, these simple technologies proved practical and effective in strengthening household food security, reducing production costs, and promoting environmental sustainability in Nagari Simawang. Keywords: microgreens, liquid organic fertilizer, botanical pesticide, food security, sustainable agriculture